If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x(7 + -1x) + 12 + 3x = 15 (7 * -3x + -1x * -3x) + 12 + 3x = 15 (-21x + 3x2) + 12 + 3x = 15 Reorder the terms: 12 + -21x + 3x + 3x2 = 15 Combine like terms: -21x + 3x = -18x 12 + -18x + 3x2 = 15 Solving 12 + -18x + 3x2 = 15 Solving for variable 'x'. Reorder the terms: 12 + -15 + -18x + 3x2 = 15 + -15 Combine like terms: 12 + -15 = -3 -3 + -18x + 3x2 = 15 + -15 Combine like terms: 15 + -15 = 0 -3 + -18x + 3x2 = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(-1 + -6x + x2) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-1 + -6x + x2)' equal to zero and attempt to solve: Simplifying -1 + -6x + x2 = 0 Solving -1 + -6x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '1' to each side of the equation. -1 + -6x + 1 + x2 = 0 + 1 Reorder the terms: -1 + 1 + -6x + x2 = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -6x + x2 = 0 + 1 -6x + x2 = 0 + 1 Combine like terms: 0 + 1 = 1 -6x + x2 = 1 The x term is -6x. Take half its coefficient (-3). Square it (9) and add it to both sides. Add '9' to each side of the equation. -6x + 9 + x2 = 1 + 9 Reorder the terms: 9 + -6x + x2 = 1 + 9 Combine like terms: 1 + 9 = 10 9 + -6x + x2 = 10 Factor a perfect square on the left side: (x + -3)(x + -3) = 10 Calculate the square root of the right side: 3.16227766 Break this problem into two subproblems by setting (x + -3) equal to 3.16227766 and -3.16227766.Subproblem 1
x + -3 = 3.16227766 Simplifying x + -3 = 3.16227766 Reorder the terms: -3 + x = 3.16227766 Solving -3 + x = 3.16227766 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = 3.16227766 + 3 Combine like terms: -3 + 3 = 0 0 + x = 3.16227766 + 3 x = 3.16227766 + 3 Combine like terms: 3.16227766 + 3 = 6.16227766 x = 6.16227766 Simplifying x = 6.16227766Subproblem 2
x + -3 = -3.16227766 Simplifying x + -3 = -3.16227766 Reorder the terms: -3 + x = -3.16227766 Solving -3 + x = -3.16227766 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = -3.16227766 + 3 Combine like terms: -3 + 3 = 0 0 + x = -3.16227766 + 3 x = -3.16227766 + 3 Combine like terms: -3.16227766 + 3 = -0.16227766 x = -0.16227766 Simplifying x = -0.16227766Solution
The solution to the problem is based on the solutions from the subproblems. x = {6.16227766, -0.16227766}Solution
x = {6.16227766, -0.16227766}
| 7x=1-11.1 | | (3/4d)-(1/2d)=2/3 | | 2z+6= | | -27=18-9u | | 2x+4x^3+4xy^2=0 | | 8x=1-0.33 | | 40+63= | | 9(8+m)=8+9m | | 5z+12= | | -5(x)=2x-5 | | 8x=1-0.67 | | 10x-2(x-1)=10 | | t=y+5 | | 5x-2-4x+1=10 | | 5(p-2)-(2p+2)=12 | | 2(3b-4)=2(r-4)-6 | | 0(x)=2x-5 | | Z/5-7=7/8 | | b(3)=b(2)+1 | | -9+8q=-41 | | 6-6r^2=-195 | | (4.47)(4^2)(3.14)1/3 | | -54=9(g-97) | | 1/2COS^2(5X) | | 75=1/3(3.14)(4^2)H | | h(4^2)(3.14)1/3 | | 68=7(x+4)+5 | | 8a-3=6a+12 | | 21x^2-x^4-80=0 | | -5.91x=-42.14421 | | 4.4y+7.1=6.4y-6.6 | | 8x=0.67 |